2015
DOI: 10.1097/md.0000000000002040
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Acute Kidney Injury and Long-Term Outcome in Patients With Acetaminophen Intoxication

Abstract: Acetaminophen (APAP) intoxication is a common cause of hepatic toxicity and life-threatening hepatic failure. However, few studies have investigated the possible association between APAP intoxication and acute kidney injury (AKI). We constructed a retrospective cohort study to clarify the relationship between APAP intoxication and the risk of AKI.We identified patients with APAP intoxication and selected a comparison cohort that was 1:4 frequency matched according to age, sex, and year of APAP intoxication dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 15 publications
1
30
1
2
Order By: Relevance
“…15 The NHIRD details have been adequately described in previous highly cited papers. 16 , 17 To ensure patient privacy, patient identification numbers are scrambled before the files are released for research. Diseases were defined according to the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes.…”
Section: Methodsmentioning
confidence: 99%
“…15 The NHIRD details have been adequately described in previous highly cited papers. 16 , 17 To ensure patient privacy, patient identification numbers are scrambled before the files are released for research. Diseases were defined according to the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes.…”
Section: Methodsmentioning
confidence: 99%
“…Previous case reports 2 - 4 and cohort studies 5 , 6 have suggested an association between supratherapeutic doses of APAP and AKI. To our knowledge, there is only one case series 7 that reported two AKI cases suspiciously induced by therapeutic-dose APAP.…”
Section: Introductionmentioning
confidence: 91%
“…При передозировке ПАР способен вызывать тяжелое поражение почек [32,33]. Но при использовании его терапевтических доз риск почечных осложнений, по-видимому, достаточно низкий.…”
Section: парацетамолunclassified